Effects of resisted sprint training on sprinting ability and change of direction speed in professional soccer players. Issue 17 (2nd September 2018) - Gil, Saulo; Barroso, Renato; Crivoi do Carmo, Everton; Loturco, Irineu; Kobal, Ronaldo; Tricoli, Valmor; Ugrinowitsch, Carlos; Roschel, Hamilton
ABSTRACT: Resisted sprint training consists of performing overloaded sprints, which may produce greater effects than traditional sprint training. We compared a resisted sprint training with overload control versus an unresisted sprint training program on performance in soccer players. Eighteen elite athletes were randomly assigned to resisted (RST) or unresisted sprint training protocol (UR). Before and after a 6-week training period, sprinting ability, change of direction speed (COD), vertical jumps (SJ and CMJ), mean power (MP) and mean propulsive power (MPP) at distinct loads were assessed. Both groups improved sprinting ability at all distances evaluated (5m: UR = 8%, RST = 7%; 10m: UR = 5%, RST = 5%; 15m: UR = 4%, RST = 4%; 20m: UR = 3%, RST = 3%; 25m: UR = 2%, RST = 3%;), COD (UR = 6%; RST = 6%), SJ (UR = 15%; RST = 13%) and CMJ (UR = 15%; RST = 15%). Additionally, both groups increased MP and MPP at all loads evaluated. The between-group magnitude-based inference analysis demonstrated comparable improvement ("trivial" effect) in all variables tested. Finally, our findings support the effectiveness of a short-term training program involving squat jump exercise plus sprinting exercises to improve the performance of soccer players.